2020
DOI: 10.1101/2020.07.21.20159178
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

SARS-CoV-2 infection induces sustained humoral immune responses in convalescent patients following symptomatic COVID-19

Abstract: Long-term antibody responses and neutralizing activities following SARS-CoV-2 infections have not yet been elucidated. We quantified immunoglobulin M (IgM) and G (IgG) antibodies recognizing the SARS-CoV-2 receptor-binding domain (RBD) of the spike (S) or the nucleocapsid (N) protein, and neutralizing antibodies during a period of six months following COVID-19 disease onset in 349 symptomatic COVID-19 patients, which were among the first world-wide being infected. The positivity rate and magnitude of IgM-S and… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

10
63
0
3

Year Published

2020
2020
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(76 citation statements)
references
References 26 publications
10
63
0
3
Order By: Relevance
“…The magnitude of the following decline in neutralizing antibody titres reported here is similar to that observed in several newly reported pre-prints 12,13,20,31,[34][35][36][37][38][39] . In these studies, similar to our observations, those who generated a high neutralizing antibody titre still had high neutralizing antibody titres regardless of the initial decline 12,13,31,35,39 and, for those with lower disease severity, two studies reported 7/34 (ref.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The magnitude of the following decline in neutralizing antibody titres reported here is similar to that observed in several newly reported pre-prints 12,13,20,31,[34][35][36][37][38][39] . In these studies, similar to our observations, those who generated a high neutralizing antibody titre still had high neutralizing antibody titres regardless of the initial decline 12,13,31,35,39 and, for those with lower disease severity, two studies reported 7/34 (ref.…”
Section: Discussionsupporting
confidence: 90%
“…31 ) individuals with a decline to undetectable neutralizing antibodies (ID 50 < 20 or ID 50 < 50, respectively) at the last timepoint studied. In contrast, several studies report a sustained antibody response in the first 3 months after SARS-CoV-2 infection, but these studies report changes in binding antibodies only 34,37,38 . Although binding titres to S glycoprotein and RBD correlate with neutralizing antibody titres, this difference in antibody measurement may account for the differences in kinetics described.…”
Section: Discussionmentioning
confidence: 92%
“…These results appear to be consistent with those obtained for other human coronaviruses, such as NL63, 229E, OC43, and HKU1, showing a rapid decay of antibodies directed against the nucleocapsid protein 16 . However, other studies showed different results, with high IgG levels after several months [7][8][9]17 . The inconsistency in the results of previous studies could be explained by differences in the study populations (i.e., patients with mild vs moderate or severe disease) or in the use of different methods (i.e., detection of antibodies directed against the nucleocapsid vs whole spike or the receptor binding domain of the spike) 4 .…”
Section: Discussionmentioning
confidence: 91%
“…Analysis of SARS-CoV-2 specific antibodies response in a cohort of COVID-19 patients in China showed a potential overall correlation between total antibodies (IgG and IgM) against the RBD and disease severity [30]. Interestingly, a recent study showed an opposite trend of increased IgG antibodies in milder cases compared to more severe COVID-19 patients [31]. However, this study focused on the correlation between antibodies levels and viral RNA shedding in patients and not necessarily disease severity.…”
Section: Discussionmentioning
confidence: 99%